Inter-American Yearbook on Human Rights / Anuario Interamericano de Derechos Humanos, Volume 12 (1996) : Volume One (Human Rights and Humanitarian Law - Book Archive pre-2000., 1998)
The print edition is available as a set of two volumes (9789041110800).